LONELINESS IN RURAL AREAS—LEARNING FROM RESEARCH, PRACTICE AND LIFE. (11th November 2018) - O'Sullivan, R; Holley, L; Ford, C
Abstract: The issue of chronic loneliness has been described as the new epidemic affecting modern society. The association between loneliness with poorer health outcomes has been well established. However, the specific issue of those reporting loneliness in rural areas has received less attention and debate. This symposium illustrates the challenges faced by seniors in rural settings in both the USA and Europe. It shines a spotlight on environmental, gender, housing, LGBTQ community, as well as mental health in rural areas in a bid to increase understanding, debate and discussion. The symposium aims to answer the question: are there particular characteristics of rural loneliness that may have implications for public health and community practice? Burholt and colleagues use data from the UK (rural Wales) to examine individual and situational risks for social loneliness and emotional loneliness. While Maiden et al in the USA study the differential experiences of men and women through a structural lens. Wiese and Williams provide deep description of the lived experience of seniors in rural social housing communities and their coping strategies. Guest uses state wide data from Kentucky to uncover the impact that loneliness has on marginalized groups and focuses on LGBTQ experiences in rural areas. Finally Jennings concludes with a community-based education program used to improve psychological well-being amongst rural elders. This interdisciplinary symposium provides a strong basis to help guide applied approaches to addressing and preventing loneliness in rural communities among older people.